Issues in measuring absolute poverty: the case of Greece - Labrindis, George; Maniatis, Thanassis; Bassiakos, Yiannis C; Passas, Costas (Argumentum, 2011)
This paper aims at revealing methodological issues referring to the definition and measurement of absolute poverty. The literature on poverty, both relative and absolute, is reviewed and a proposal is put forth for an approach of absolute poverty based on needs and the notion of the value of labour power. The paper presents the results of the application of this method in the Metropolitan Athens area.